Mitosis and meiosis how cells divide. (Makati, Metro Manila Felta, 1986)
Using photomicrographs and computer-generated graphics, analyzes the chain of events that results in cell division. Demonstrates each phase of mitosis and meiosis, traces their roles in asexual and sexual reproduction, and looks at the consequences of abnormal cell division.
Keywords: Mitosis; Meiosis; Cell division; Mitosis; Meiosis; Cell division; Cells